2018
DOI: 10.1111/rssa.12385
|View full text |Cite
|
Sign up to set email alerts
|

Misspecification of Multimodal Random-Effect Distributions in Logistic Mixed Models for Panel Survey Data

Abstract: Summary Logistic mixed models for longitudinal binary data typically assume normally distributed random effects, which may be too restrictive if an underlying subpopulation structure exists. The paper illustrates the ease of implementing diagnostic tests and fitting random effects as a mixture of normal distributions to detect and address distributional misspecification of the random effects in a potential mover–stayer scenario. Methods are illustrated by using data from the Household, Income and Labour Dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…However, many researchers have been concerned that the incorrect assumption may lead to substantial asymptotic bias in the maximum likelihood estimates of the regression parameters when the assumption for a random effect is violated. [9][10][11][12] Moreover, the type I error and the power for a test associated with regression parameter are also affected. 13,11 Various inferential methods have been developed to address the misspecification issues (for example, see 14,15,10,1 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, many researchers have been concerned that the incorrect assumption may lead to substantial asymptotic bias in the maximum likelihood estimates of the regression parameters when the assumption for a random effect is violated. [9][10][11][12] Moreover, the type I error and the power for a test associated with regression parameter are also affected. 13,11 Various inferential methods have been developed to address the misspecification issues (for example, see 14,15,10,1 ).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Verbeke and Molenberghs (2013) illustrated the use of the gradient function method combined with a finite mixture of normals, proposed by Verbeke and Lesaffre (1996), instead of using the simple normality assumption on random-effects distribution. Although mixtures of normals are very flexible and may offer very simple interpretations, 11,12 it is often difficult to obtain stable solutions. Therefore, it was suggested that a finite mixture of normals for random-effects distributions could be incorporated into a general sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was suggested that a finite mixture of normals for random-effects distributions could be incorporated into a general sensitivity analysis. 5 Insights from the gradient function can be utilized in model construction in this framework, 11,12 and can also be applied to research involving joint modeling of longitudinal measurements and survival time. 13 In addition to the normality assumption, dependence of the random-effects variance on covariates is also an important issue.…”
Section: Introductionmentioning
confidence: 99%